ฮูปแต้มวรรณกรรมปฐมสมโพธิกถาในศาสนาคารอีสาน - นนตรี, พระวโรตม์ (วารสาร ศึกษาศาสตร์ มมร; Vol 5 No 1 (2017): วารสารศึกษาศาสตร์ มมร ปีที่ 5 ฉบับที่ 1 (มกราคม-มิถุนายน 2560), 2018)
ศาสนาคารหรืออาคารอันเกี่ยวกับศาสนา ได้แก่ โบสถ์ เป็นที่ประกอบพิธีกรรมของชุมชน ศิลปินจึงใช้พื้นที่ของศาสนาคารเพื่อถ่ายทอดเรื่องราวทั้งวรรณกรรมและจิตรกรรม หรือ “ฮูปแต้ม” ให้ประชาชนทั่วไปสามารถเข้าใจ โดยเฉพาะวรรณกรรมที่ชาวอีสานรู้จักกัน คือ สินไซ ผะเหวด พะลักพะลามและปฐมสมโพธิ แม้วรรณกรรมเรื่องอื่น  ๆ จะเขียนไว้ภายนอกตัวศาสนาคาร แต่ในพื้นที่ภาคอีสานนั้นพบตัวอย่างฮูปแต้มที่ได้รับอิทธิพลวรรณกรรมปฐมสมโพธิกถา ปรากฏ “แต้ม” เขียนไว้ภายในศาสนาคารหรือ “สิม” ซึ่งแตกต่างจากวรรณกรรมเรื่องอื่น  ๆ ที่มักเขียนไว้ที่ผนังภายนอกตัวสิม แสดงให้เห็นถึงความเป็นภาพศักดิ์สิทธิ์ภายในพื้นที่ศักดิ์สิทธิ์ Abstract A religious building or a building used in connection with religion, i.e. a chapel, is a ceremonious place for community worship. Local artists rely heavily on such buildings to express their ideas to the public through literature and painting, or “hoop taem”, especially through folklores generaly known among Nortestern people such as Sin Sai, Pra Wed, Pra-lak Pa-lam and Pa-dhomsombhod,. Folklore paintings are generally depicted on the external wall of the religious building while the “hoop taem” narrating Pa-dhomsombhod folklore is often found to be “taem” or painted – on the interior wall of the religious building, or know locally as “Sim”. Such occurrence is different from its counterparts which are often found to be painted outside. This indicateds the sacredness of such painting expressed inside a sanctity